Development of a Student Behavior Rating Scale According to Hellisons’ Model - Nikopoulou Μαρία; Tsitskaris Γεώργιος; Doganis Γεώργιος; Kioumourtzoglou Ευθύµης (Inquiries in Physical Education and Sport, 2006)
The purpose of the study was to develop, validate and establish the reliability of a student behavior rating scale both during physical education (PERS) and classroom lessons (CRS), according to Hellison’s model. Firstly, relevant behaviors were collected and given to three Sport Psychology professors for the evaluation of content validity. Secondly, 264 students of a Multicultural High school completed the final PERS in order to test the construct validity and reliability of the scale. Results from the factor analysis yielded six factors, accounting for 74.78% of the variance. Coefficient Alpha reliability appeared to be high for the factors: Irresponsibility (a=.81), Cooperation (a=.80), Goal (a=.82), Effort (a=.84) and medium for the Participation (a=.74) and Assistance (a = .62). Third, two teachers modified the physical education rating scale with behaviors that students show during classroom lessons (CRS). The CRS were given to four high school teachers who evaluated 92 students, 23 each. The factor analysis of teachers’ evaluation revealed five factors, accounting for 73.4% of the variance. Coefficient Alpha reliability appeared to be high for most of the factors: Participation (a= .97), Irresponsibility (a= .92), Cooperation (a= .93), Multicultural Cooperation (a= .94) and medium for Assistance (a = .79).